A new map of Denmark and Sweden: according to ye newest and most exact observations - Moll, Herman; Robinson, John. ([London]: printed for H. Moll over against Devereux Court without Temple Bar in the Strand Iohn Bowles at the Black Horse in Cornhill, Thomas Bowles print & mapseller next to the Chapter House in St. Pauls Church yard and by Philip Overton map & printseller near S. Dunstans Church Fleetstreet, 1712, 1712)
Janamittakaavat: Miles of Great Britain Denish and Swedish miles German leagues. Dedikaatio: To his excellency John, Lord Bishop of Bristol, Ld. Privy Seal, and her majesty's first plenipotentiary at the treaty of Utrecht, this map is humbly dedicated by your excellency's most humble servant H. Moll. 0-meridiaanit: Lontoo ja Ferro. Sisältää myös viisi Johannes Schefferuksen teokseen Lapponia perustuvaa kuvaa: The Laplanders. Sisältää kartakkeen The north part of Norway, Lapland and Greenland [i.e. Spitsbergen]. Liittyy teokseen The World Described /Herman Moll.